2023
DOI: 10.1007/s11218-023-09761-7
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing the diversity in how students define belonging: evidence of differing conceptualizations, including as a function of students’ gender and socioeconomic background

Abstract: Sense of belonging is a fundamental human motivation and, in higher education settings, has been associated with students’ motivation and academic outcomes. However, less is known about the nuances of how students define belonging within a university context, and how their gendered and socio-economic identity-based experiences inform these definitions. Using a qualitative approach, we interviewed 36 UK university students to better understand (1) students’ definitions of belonging to university, and (2) how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 101 publications
0
9
0
Order By: Relevance
“…Latent mean comparisons showed AAPI students exhibited lower levels of CC than White peers, and regression analyses suggested that attaining the CC that is rewarded at a PWI may incur costs for life satisfaction, particularly for AAPI students. As noted by others, attainment of this CC may both be especially relevant for minoritized students in developing a sense of belonging (Fernández et al, 2023) and pose an additional burden for minoritized students (e.g., Isserles & Dalmage, 2000;Strayhorn, 2010Strayhorn, , 2018. Scholars have posited, in fact, that developing a sense of belonging within structurally racist institutions may not be a wholly positive thing, even if it is positively associated with academic attainment (Stokes, 2023).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Latent mean comparisons showed AAPI students exhibited lower levels of CC than White peers, and regression analyses suggested that attaining the CC that is rewarded at a PWI may incur costs for life satisfaction, particularly for AAPI students. As noted by others, attainment of this CC may both be especially relevant for minoritized students in developing a sense of belonging (Fernández et al, 2023) and pose an additional burden for minoritized students (e.g., Isserles & Dalmage, 2000;Strayhorn, 2010Strayhorn, , 2018. Scholars have posited, in fact, that developing a sense of belonging within structurally racist institutions may not be a wholly positive thing, even if it is positively associated with academic attainment (Stokes, 2023).…”
Section: Discussionmentioning
confidence: 97%
“…This article is intended solely for the personal use of the individual user and is not to be disseminated broadly. , Fernández et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations